2019
DOI: 10.13057/biodiv/d200332
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of gender equity in household: A case from a peatland-based community in Riau, Indonesia

Abstract: Abstract. Herawati T, Rohadi D, Rahmat M, Winarno B. 2019. An exploration of gender equity in household: A case from a peatland-based community in Riau, Indonesia. Biodiversitas 20: 853-861. Gender roles in peatland-based communities’ livelihoods are an important factor in livelihood vulnerability due to challenging characteristics for conducting agriculture in this area. This article reports on a study of gender roles in Riau Province in 7 villages in 3 districts, aiming to identify significant attributes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The groups represent those most affected by climate change (Wagey, 2018), but their role, participation, and contribution in land management and environmental conservation has been underrepresented and underappreciated. Herawati et al (2019) indicated that peatland management is dominated by men, but women have a role in physical activities and decision-making in land management. In the PAR process, two women farmer groups collectively managed 3.3 ha of pineapple agroforestry to support peatland restoration and to provide livelihood and wellbeing improvements.…”
Section: Introductionmentioning
confidence: 99%
“…The groups represent those most affected by climate change (Wagey, 2018), but their role, participation, and contribution in land management and environmental conservation has been underrepresented and underappreciated. Herawati et al (2019) indicated that peatland management is dominated by men, but women have a role in physical activities and decision-making in land management. In the PAR process, two women farmer groups collectively managed 3.3 ha of pineapple agroforestry to support peatland restoration and to provide livelihood and wellbeing improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of the 5Rs approach requires appropriate local community capacity building to be undertaken by local government or NGOs, and establishment of community working groups at the village level. Women and youth participation in community working groups and restoration activities should be fostered, given their active role in household income generation in peatland areas (Herawati et al 2019). Indigenous people living in and adjacent to peatlands have been shown to be effective stewards for these ecosystems and custodians of traditional knowledge, and their engagement should comply with Free, Prior and Informed Consent principle.…”
Section: Discussionmentioning
confidence: 99%
“…Peatland ecosystem resilience is inextricably linked to the well‐being of the communities living within them (Herawati et al 2019). In Indonesia, 75% of peatlands are in community (nonconcession) land (MOEF 2018), where approximately 16.3 million people residing within and dependent on forest and peatland areas (Puspitaloka et al 2020).…”
Section: Proposed Community‐led Restoration Approach: 5rs Approachmentioning
confidence: 99%
“…Meanwhile, the role of women was described as more responsible for managing activities at home". (Herawati, Rohadi, Rahmat, & Winarno, 2019).…”
Section: Master Mentalitymentioning
confidence: 99%